Patrimônio arqueológico musealizado em Sergipe : um estudo de caso sobre a relação documentação museológica e informação arqueológica como procedimento essencial de gestão de coleções - Santos, Heide Roviene Santana dos (2015)
This study deals with the archaeological heritage management, specifically the management of information related to collections that received endorsement of museum institutions linked to Federal University of Sergipe (UFS), namely: Archaeology Museum of Xingó (MAX) and collections from Museum of Man of Sergipe (MUHSE). In granting the institutional endorsement to archaeology projects under contract, these institutions became responsible for vast amount of collections. Thinking about the archaeological heritage as a source of information, the objective of this study is to analyze the mechanisms made for information management concerning the collections of archaeological field collected under contract archaeology, and under the custody of museums in the Federal University of Sergipe, as well how to check if these procedures - if any - interact with the guidelines of the areas of Archaeology and Museology in relation to collections management. In front of the collections in the custody of the UFS, and the need for realization of management procedures for the archaeological heritage, this study assumes that it is imperative structuring mechanisms that permeate from the act of acquisition to the dissemination of information collections. This planning will be more complicated under the absence of several actions that prevent the collections management, especially if it occurs during the archaeological “rescue”. Lastly, the social role of museum institutions for knowledge of information in relation with archaeological heritage is consider, highlighting the necessity of implementing the museum documentation procedure on the archaeological collections, both by museum institutions as in field work, where these management mechanisms will enable the dissemination of information belonging to these cultural objects that are liable to be interpreted as acts and voices of past people to understand the social practices of present.